The Role of Women in Increasing the Added Value of Cashew Agroindustry (Anacardium occidentale L.) (Gender Analysis in Cashew Agroindustry In Mojokerto – East Java) - Ida Agustini Saidi; Dwi Asmarawati (Universitas Muhammadiyah Sidoarjo, 2010)
Aim of this research were to analyze added value of cashew agroindustry and to identiy and map women strength and weakness in every step, pre production; production; and post production in cashew agroindustry system in Mojokerto regency. The research was carried out since Apri unti October 2007. Research location in Ngoro district was determined based on highest Location Potential index. Among 6 (six) villages have cashew potency, Wonosari village was determined as sample location, as it has greatest number of home agroindustries. Samples of this research was made by census. Data was analyzed by agroindustry added value analyzes and strength and weakness analyzes by Matrics of Disagregated Capacities and Vulnerabilities. Result of the research showed that cashew agroindustry gives added value per 1 kg cashew nut by 22,22 %, which is 40 % as labour share, and 60 % as profit. Women and men take parts in pre production, production, and post production, with greater women participation. Women weakness in agroindustry comprises of capital and information acces; working hours that is often disturbed by domestic activity; and afraid to expand the business. Within production inputs as nowadays condition, there is no tendency of women marginalization.